Formation of Ozone in the tropospheric (Journal of Academic Research, 2022)
Tropospheric ozone (O3) is formed via transport from stratospheric O3 and by oxidation of carbon monoxide (CO) and volatile organic compounds (VOCs) in the presence of NOx (NO + NO2). In fact, presence of NOx is important in formation of O3. In the presence of VOCs and NOx, chlorine atoms also play a role in the formation of tropospheric O3. Monitoring the concentration of O3 in the troposphere "where we live" is very important and that is due to its effect on human's health as well as agricultural crops.